The Twelfth-century documents of St. George’s of Tròccoli (Sicily) - von Falkenhausen, V; Jamil, N; Johns, J (University of Bergen, 2017)
This study publishes for the first time six authentic and original documents from mid-twelfth-century Nor-man Sicily. Three are bilingual, written in Greek and Arabic, and three are Arabic. All were issued by the multilingual dīwān of King Roger de Hauteville and relate to the lands and Muslim peasants held of the crown by the Greek monastery of St. George’s of Tròccoli, near Caltabellotta. These documents are of particular interest in four principal ways. First, they permit the reconstruction in unusual detail of the inter-nal administrative processes of the royal dīwān. Second, they preserve the toponymy and describe the topography of the lands of St. George’s that lay in a district of Norman Sicily until now poorly documented. Third, they record the remarkable phenomenon of the immigration to Norman Sicily of Muslims, who apparently commended themselves into the service of a Christian monastery as villeins, in order to escape deprivation and famine in Ifrīqiyya. And fourth, they add to the small corpus of Arabic documents from Norman Sicily, contributing much new evidence for their diplomatic form, language and palaeography.